2020
DOI: 10.1007/s12671-020-01344-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Acceptance and Commitment Therapy and Mindfulness-Based Stress Reduction Self-Help Books for College Student Mental Health

Abstract: Objectives: Self-help has the potential to improve access to mental health resources for college students. However, solutions are needed to improve sustainable delivery, cost-effectiveness, and to know which resources are most useful. Methods: A sample of 109 college students were randomly assigned to read either an Acceptance and Commitment Therapy (ACT) or Mindfulness-Based Stress Reduction (MBSR) self-help book through the University library website over 8 weeks with assessments at baseline, midtreatment (4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 34 publications
1
5
0
3
Order By: Relevance
“…Positive mental health was significantly improved relative to the WLC at posttest ( d = 0.59), and this effect remained at the 3‐month follow‐up ( d = 0.39). This result is consistent with previous studies which found that the iACT interventions could not only reduce depressive symptoms, but also improve participants' positive mental health (Levin, An, et al, 2020; Levin, Krafft, et al, 2020; Pots et al, 2016).…”
Section: Discussionsupporting
confidence: 92%
“…Positive mental health was significantly improved relative to the WLC at posttest ( d = 0.59), and this effect remained at the 3‐month follow‐up ( d = 0.39). This result is consistent with previous studies which found that the iACT interventions could not only reduce depressive symptoms, but also improve participants' positive mental health (Levin, An, et al, 2020; Levin, Krafft, et al, 2020; Pots et al, 2016).…”
Section: Discussionsupporting
confidence: 92%
“…College students may gain benefits from online telemedicine to improve wellness and boost coping strategy such as empathic listening, psychoeducation, or supportive therapy (Hatta, 2020). Some studies have shown that self-help mindfulness therapy can improve psychological distress, positive mental health, and academic distress in college students, as well as what was expected to increase resilience and reduce depression anxiety and stress in other adults who need psychotherapy (Javedani et al, 2017;Levin et al, 2020). In addition, the society, colleges and universities, families, and students should take effective actions in time to prevent the occurrence of adverse psychology of college students during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated the benefits of ACT-based interventions for non-suicidal self-injury ( Callahan et al, 2021 ), PTSD symptoms ( Grau et al, 2020 ), and PI ( Pakenham et al, 2020 ). Given the particular situation of the COVID-19 pandemic, ACT self-help books or online ACT interventions could be effectively employed ( Huang et al, 2021 ), which have proved to be effective in prior studies ( Probst et al, 2019 ; Levin et al, 2020 ). Evidence-based interventions using (online) ACT or other strategies to mitigate PI and improve mental health in different populations is also warranted.…”
Section: Discussionmentioning
confidence: 99%